Intercellular adhesion molecule-1 and CD36 synergize to mediate adherence of Plasmodium falciparum-infected erythrocytes to cultured human microvascular endothelial cells. - McCormick, C; Craig, A; Roberts, D; Newbold, C; Berendt, A (1997)
We have compared the adhesion of Plasmodium falciparum-infected erythrocytes to human dermal microvascular endothelial cells (HDMEC) and human umbilical vein endothelial cells (HUVEC) and have assessed the relative roles of the receptors CD36 and intercellular adhesion molecule-1 (ICAM-1). HUVEC (a cell line that expresses high levels of ICAM-1 but no CD36) mediate low levels of adhesion, whereas HDMEC (which constitutively express CD36) mediate high levels of adhesion even before ICAM-1 induction ICAM-1 expression leads to yet greater levels of adhesion, which are inhibited both by anti-ICAM-1 and CD36 mAbs, despite no increase in the expression of CD36. The results indicate the presence of a substantial population of infected cells that require the presence of both receptors to establish adhesion. Synergy between these receptors could be demonstrated using a number of parasite lines, but it could not be predicted from the binding of these same parasite lines to purified ICAM-1 and CD36. This phenomenon could not be reproduced using either purified receptors presented on plastic, or formalin-fixed HDMEC, suggesting that receptor mobility is important. This is the first study to demonstrate receptor synergy in malaria cytoadherence to human endothelial cells, a phenomenon necessary for parasite survival and associated with disease severity.